Determinants of Breast Cancer Screening Among Reverend Sisters in Kampala Archdiocese, Uganda: A Cross-Sectional Study - Kaddu, Judith; Basaza, Robert; Otienob, Emmanuel; Mirembea, Florence (Archives of Breast Cancer, 2022)
Background: Breast cancer in Uganda is the second commonest cancer in women coming only next to cancer of the cervix. This is the first cross-sectional study to investigate the determinants of self-breast cancer screening among Reverend Sisters in Kampala, the largest Archdiocese of Roman Catholic Church in Uganda. The prevention strategies in this country are still not optimal and the key to prevention is breast screening. Methods: A cross-sectional analytical study was conducted from September, 2018 to June, 2019. A sample of 310 respondents were interviewed using a semi-structured, self administered questionnaire. Data was analyzed using logistic regression model. Results: A majority (96.4%) of the respondents did not do a mammography, 54.1% never practiced breast self-examination (BSE) and 34.2% performed it regularly during bedtime. The reasons for performing BSE included: curiosity (61.9%), having a lump (19%) and carrying out screening (9.5%). Significant predictors of breast cancer screening were ordinary level of education (11 years of education), hearing about breast cancer, different screening methods, and symptoms of breast cancer, usefulness of screening for women, a need for sisters to screen, self-breast examination and mammography. Age and other levels of education were not significantly associated with breast cancer screening. Conclusion: The Reverend Sisters had a low level of knowledge and a small fraction practiced breast cancer screening. This demands a sustainable interventional strategy of breast health awareness campaign, establishment of appropriate health infrastructure related to precision oncology in Uganda and similar settings.